Method for separating positive electrode materials from waste lithium-ion batteries
By mixing the positive electrode sheet, easy-to-decompose carbonate and sodium hydroxide of waste lithium-ion batteries, efficient separation of the positive electrode material and aluminum foil is achieved, solving the problems of difficulty in separation and environmental pollution in traditional methods, and achieving high efficiency and environmental protection The cathode material is recovered.
Patent Information
- Application Number
- CN202410442923.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-12
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-04-12
AI Technical Summary
The prior art is difficult to efficiently separate the positive electrode material in waste lithium-ion batteries, especially because the bonding agent between the positive electrode material and the aluminum foil is tightly connected, making it difficult to separate. In addition, the traditional method requires high temperature gasification of the adhesive or toxic waste gas. .
By mixing the positive electrode sheet, easy-to-decompose carbonate and sodium hydroxide of waste lithium-ion batteries and heating, the temperature rises and turns the binder and sodium hydroxide into liquid, corroding the aluminum foil and generating carbon dioxide bubbles, expanding the gap between the aluminum foil and the positive electrode material. , and achieve separation with screening.
It reduces separation temperature and energy consumption, avoids the generation of waste gas and wastewater, is friendly to the environment, and does not affect the chemical properties of the cathode material, creating conditions for its reuse, and the separation rate is as high as more than 95%.
Smart Images

Figure CN118248979B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of waste lithium ion recovery and treatment, and in particular to a method for separating positive electrode materials from waste lithium ion batteries. Background Art
[0002] Lithium-ion batteries have been widely used in mobile smart terminals, small electrical equipment, grid energy storage devices, electric vehicles and other electronic devices due to their advantages such as high voltage, high energy density and good cycle performance. With the increasing demand for battery quality and quantity in downstream industries, especially the power battery industry, lithium-ion batteries have become one of the current research hotspots.
[0003] Lithium-ion batteries use a large amount of metal materials, such as lithium, nickel, cobalt, manganese, copper, iron and aluminum. Therefore, used lithium-ion batteries contain rich valuable metals. Among them, the positive electrode material of the battery is an important component of lithium-ion batteries and also concentrates most of the valuable metal resources, so it has a higher recycling value.
[0004] Generally speaking, the recycling methods of waste lithium-ion batteries include: discharge treatment, disassembly treatment, separation of active substances containing aluminum foil, dissolution treatment and resynthesis of new materials; and among these steps, separation of active substances containing aluminum foil is one of the key links to achieve efficient recycling of lithium-ion batteries. The adhesion between graphite particles and copper foil in waste lithium-ion batteries is low, so graphite can be easily recovered through mechanical treatment. In contrast, the more valuable positive electrode material and aluminum foil are usually tightly connected together by organic binders, so it is more difficult to separate.
[0005] The above contents are only used to assist in understanding the technical solution of the present application and do not constitute an admission that the above contents are prior art. Summary of the invention
[0006] The main purpose of the present application is to provide a method for separating positive electrode materials from waste lithium-ion batteries, aiming to solve or at least partially solve the technical problem of the difficulty in separating positive electrode materials from waste lithium-ion batteries.
[0007] To achieve the above object, the present application provides a method for separating positive electrode materials from waste lithium-ion batteries, the method comprising the following steps:
[0008] The positive electrode sheet of the waste lithium-ion battery, easily decomposable carbonate and sodium hydroxide are mixed and heated to obtain a mixed material;
[0009] The mixed material is screened to obtain separated positive electrode materials.
[0010] Optionally, the decomposition temperature of the easily decomposable carbonate is 200-500°C.
[0011] Optionally, the easily decomposable carbonate includes at least one of zinc carbonate, magnesium carbonate, copper carbonate and nickel carbonate.
[0012] Optionally, the heating temperature is 320-500°C.
[0013] Optionally, the heating time of the heating is: 20-60 min.
[0014] Optionally, the mass ratio between the positive electrode sheet and the easily decomposable carbonate is 1:(1-5).
[0015] Optionally, the mass ratio between the positive electrode sheet and the sodium hydroxide is 1:(2-10).
[0016] Optionally, the step of mixing and heating the positive electrode sheet of the waste lithium-ion battery, the easily decomposable carbonate and the sodium hydroxide to obtain the mixed material comprises:
[0017] The positive electrode sheet, the easily decomposable carbonate and the sodium hydroxide are mixed and heated, and then kept warm for 10-30 minutes to obtain the mixed material.
[0018] Optionally, the positive electrode sheet includes: at least one of a lithium iron phosphate positive electrode sheet, a nickel cobalt manganese positive electrode sheet and a lithium cobalt oxide positive electrode sheet.
[0019] Optionally, before the step of mixing and heating the positive electrode sheet of the waste lithium-ion battery, the easily decomposable carbonate and the sodium hydroxide, the method further comprises:
[0020] Mechanically disassembling the waste lithium-ion battery to obtain an original positive electrode sheet;
[0021] The original positive electrode sheet is cut into pieces of a preset size to obtain the positive electrode sheet.
[0022] The present application discloses a method for separating positive electrode materials from waste lithium ion batteries. The method comprises the following steps: mixing and heating positive electrode sheets of waste lithium ion batteries, easily decomposable carbonates and sodium hydroxide. As the temperature rises and reaches the melting point of the binder, the binder in the positive electrode sheets changes from a solid state to a liquid state, thereby weakening the bonding force and causing micro cracks to appear between the aluminum foil of the positive electrode sheets and the positive electrode materials. As the temperature further rises and reaches the melting point of the sodium hydroxide, the sodium hydroxide also changes from a solid state to a liquid state. At this time, the sodium hydroxide flows into the micro cracks between the aluminum foil and the positive electrode materials and begins to corrode the surface of the aluminum foil in small amounts, thereby increasing the gap between the aluminum foil and the positive electrode materials. More easily decomposable carbonates enter the gaps and generate carbon dioxide bubbles through the decomposition of the carbonates, thereby further increasing the gap between the aluminum foil and the positive electrode materials, and finally separating the aluminum foil and the positive electrode materials to obtain a mixed material. The mixed material is then screened to obtain separated positive electrode materials, thereby realizing separation and recovery of the positive electrode materials. Since the heating temperature in the separation process only needs to reach the decomposition temperature of the easily decomposable carbonate, there is no need to gasify the binder, so the separation temperature is greatly reduced, thereby reducing the energy consumption in the separation process; and no waste gas or waste water is generated in the process, which is environmentally friendly and will not affect the chemical properties of the positive electrode material, creating favorable conditions for the subsequent reuse of the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 A schematic flow chart of a method for separating positive electrode materials from waste lithium-ion batteries according to an embodiment of the present application;
[0024] Figure 2 A process flow chart of a method for separating positive electrode materials from waste lithium-ion batteries according to an embodiment of the present application;
[0025] Figure 3 This is the energy spectrum of the positive electrode material separated in Example 1 of the present application.
[0026] The realization of the purpose, functional features and advantages of this application will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0028] In addition, the meaning of "and / or" appearing in the full text includes three parallel solutions. Taking "A and / or B" as an example, it includes solution A, solution B, or a solution that satisfies both A and B. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in this field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by this application. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0029] Generally speaking, the positive electrode of a lithium-ion battery includes a positive electrode material and an aluminum foil, and polyvinylidene fluoride (PVDF) is used as a binder between the positive electrode material and the aluminum foil. In order to separate the positive electrode material and the aluminum foil, the binder can be vaporized under high temperature conditions, that is, the heating temperature needs to reach above 550 °C; but this method requires high energy consumption; and toxic gases such as dioxins will be produced during the heating process, causing environmental pollution. You can also use organic solvents such as N, N-dimethylformamide and N-methylpyrrolidone to soak the positive electrode sheet to separate the positive electrode material and the aluminum foil; but this method will produce a large amount of organic wastewater. Alternatively, the positive electrode sheet can be quickly cooled with liquid nitrogen and then crushed, and aluminum can be recovered by electrical separation after crushing, but this method also consumes a lot of energy during the separation process.
[0030] In view of this, the present application proposes a method for separating positive electrode materials from waste lithium-ion batteries, which comprises mixing and heating positive electrode sheets of waste lithium-ion batteries, easily decomposable carbonates and sodium hydroxide. As the temperature rises and reaches the melting point of the binder, the binder in the positive electrode sheet changes from solid to liquid, so that the bonding force becomes weaker and micro-cracks appear between the aluminum foil of the positive electrode sheet and the positive electrode material; as the temperature further rises and reaches the melting point of sodium hydroxide, the sodium hydroxide also changes from solid to liquid; at this time, the sodium hydroxide flows into the micro-cracks between the aluminum foil and the positive electrode material, and begins to corrode the surface of the aluminum foil in small amounts, so that the gap between the aluminum foil and the positive electrode material is enlarged, and more easily decomposable carbonates enter the gaps, and produce carbon dioxide bubbles through the decomposition of the carbonates, which further increases the gap between the aluminum foil and the positive electrode material, and finally separates the aluminum foil and the positive electrode material to obtain a mixed material; and then the mixed material is screened to obtain separated positive electrode materials, thereby realizing the separation and recovery of the positive electrode materials. Since the heating temperature in the separation process only needs to reach the decomposition temperature of the easily decomposable carbonate, there is no need to gasify the binder, so the separation temperature is greatly reduced, thereby reducing the energy consumption in the separation process; and no waste gas or waste water is generated in the process, which is environmentally friendly and will not affect the chemical properties of the positive electrode material, creating favorable conditions for the subsequent reuse of the positive electrode material.
[0031] The first aspect of the present application provides a method for separating positive electrode materials from waste lithium-ion batteries, referring to Figure 1 , the method for separating positive electrode materials from waste lithium-ion batteries includes:
[0032] Step S10, mixing and heating the positive electrode sheet of the waste lithium-ion battery, the easily decomposable carbonate and the sodium hydroxide to obtain a mixed material;
[0033] In a feasible embodiment, the positive electrode sheet includes a positive electrode material, an aluminum foil, and a binder disposed between the positive electrode material and the aluminum foil; the positive electrode sheet of the waste lithium-ion battery, an easily decomposable carbonate, and sodium hydroxide are mixed, and the mixture is heated. After the temperature reaches the melting point of the binder, the binder changes from a solid state to a liquid state; as the temperature further increases and reaches the melting point of the sodium hydroxide, the sodium hydroxide also changes from a solid state to a liquid state. At this time, the sodium hydroxide begins to corrode the surface of the aluminum foil in small amounts, so that the gap between the aluminum foil and the positive electrode material increases, and more easily decomposable carbonate enters the gap; at the same time, the easily decomposable carbonate decomposes in a high temperature environment and produces carbon dioxide bubbles, so that the gap between the aluminum foil and the positive electrode material is further increased, and finally the aluminum foil and the positive electrode material are separated to obtain a mixed material, wherein the separation rate of the positive electrode material and the aluminum foil is greater than 95%.
[0034] In one feasible implementation, before the step of mixing and heating the positive electrode sheet of the waste lithium-ion battery, the easily decomposable carbonate and the sodium hydroxide in step S10, the method further includes:
[0035] Step A10, mechanically disassembling the waste lithium-ion battery to obtain an original positive electrode sheet;
[0036] Step A20, cutting the original positive electrode sheet into pieces of a preset size to obtain the positive electrode sheet.
[0037] In a feasible embodiment, the waste lithium-ion batteries are mechanically disassembled to obtain original positive electrode sheets. At this time, the sizes of the positive electrode sheets of each waste lithium-ion battery are different. In order to improve the subsequent separation efficiency of positive electrode materials, the positive electrode sheets are cut into pieces of preset sizes to obtain original positive electrode sheets.
[0038] Optionally, the preset size may be 1-10 mm.
[0039] In this embodiment, the positive electrode sheets in the waste batteries are pre-cut into preset sizes to improve the subsequent separation efficiency of the positive electrode materials.
[0040] In one feasible embodiment, the heating temperature is 320-500°C; for example, the heating temperature is 320°C, 340°C, 360°C, 380°C, 400°C, 420°C, 440°C, 460°C, 480°C, 500°C, etc.
[0041] Since the binder between the positive electrode material and the aluminum foil is mostly an organic binder, such as PVDF; in order to convert the binder from solid to liquid, the heating temperature needs to be higher than the melting point of the binder. At the same time, in order for sodium hydroxide to bring easily decomposed carbonates into the gaps and corrode the surface of the aluminum foil, it is necessary to convert sodium hydroxide from solid to liquid, so the heating temperature also needs to be higher than the melting point of sodium hydroxide. Therefore, the heating temperature is determined to be greater than or equal to 320 °C. However, if the heating temperature is too high, it will not further promote the reaction and will also increase energy consumption. Therefore, the heating temperature is determined to be less than or equal to 500 °C.
[0042] In a feasible implementation manner, the heating time of the heating is: 20-60 min; for example, the heating time is 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, 60 min, etc. If the heating time is too short, the gap between the aluminum foil and the positive electrode material may be too small, making it difficult to completely separate the aluminum foil and the positive electrode material; and if the heating time is too long, since sodium hydroxide can corrode the aluminum foil, it may cause severe corrosion to the aluminum foil; in order to completely separate the aluminum foil and the positive electrode material and avoid a large amount of reaction between sodium hydroxide and the aluminum foil, the heating time of the heating is determined to be: 20-60 min.
[0043] In one feasible implementation, step S10, the step of mixing and heating the positive electrode sheet of the waste lithium-ion battery, the easily decomposable carbonate and the sodium hydroxide to obtain the mixed material comprises:
[0044] Step S11, mixing the positive electrode sheet, the easily decomposable carbonate and the sodium hydroxide, heating them, and then keeping the temperature for 10-30 minutes to obtain the mixed material.
[0045] In a feasible embodiment, the positive electrode sheet, the easily decomposable carbonate and the sodium hydroxide are mixed and heated, and after reaching a preset temperature, the temperature is kept for 10-30 minutes to allow the substances to fully react.
[0046] Optionally, the insulation time can be 10 min, 15 min, 20 min, 25 min, 30 min, etc. Through insulation, sufficient reaction time is given to each substance to achieve effective separation of the positive electrode material and the aluminum foil.
[0047] In a feasible embodiment, the decomposition temperature of the easily decomposable carbonate is 200-500° C., that is, an easily decomposable carbonate with a decomposition temperature between 200-500° C. is used, so that the carbonate can be effectively decomposed during the heating process to generate carbon dioxide.
[0048] Specifically, the easily decomposable carbonate is selected according to the heating temperature, that is, the decomposition temperature of the easily decomposable carbonate is less than or equal to the heating temperature.
[0049] In a feasible embodiment, the easily decomposable carbonate includes at least one of zinc carbonate, magnesium carbonate, copper carbonate and nickel carbonate.
[0050] In a feasible embodiment, the mass ratio between the positive electrode sheet and the easily decomposable carbonate is 1:(1-5); for example, the mass ratio between the positive electrode sheet and the easily decomposable carbonate is 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5, etc. If the amount of easily decomposable carbonate added is too small, it may cause insufficient bubbles to be generated, so that the positive electrode material and the aluminum foil cannot be completely separated; and if the amount of easily decomposable carbonate added is too large, it will not further promote the reaction and will also increase the cost; therefore, the mass ratio between the positive electrode sheet and the easily decomposable carbonate is determined to be 1:(1-5).
[0051] In a feasible embodiment, the mass ratio between the positive electrode sheet and the sodium hydroxide is 1:(2-10); for example, the mass ratio between the positive electrode sheet and the sodium hydroxide is 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, etc. If the amount of sodium hydroxide added is too little, it may cause bubbles to be difficult to enter between the aluminum foil and the positive electrode material, making it impossible to completely separate the positive electrode material from the aluminum foil; and if the amount of sodium hydroxide added is too much, it will not further promote the reaction and will also increase the cost; therefore, the mass ratio between the positive electrode sheet and the sodium hydroxide is determined to be 1:(2-10).
[0052] In a feasible embodiment, the positive electrode sheet includes: at least one of a lithium iron phosphate positive electrode sheet, a nickel cobalt manganese positive electrode sheet and a lithium cobalt oxide positive electrode sheet. The present application can be applied to the separation of positive electrode sheets of various lithium ion batteries.
[0053] Step S20, screening the mixed material to obtain separated positive electrode material.
[0054] In a feasible embodiment, the positive electrode material and the aluminum foil in the mixed material have been separated, so the separated positive electrode material and the aluminum foil can be obtained by screening.
[0055] For example, refer to Figure 2, step B10, the positive electrode sheet includes: a positive electrode material and an aluminum foil, and the positive electrode material and the aluminum foil are bonded together by a PVDF binder; step B20, the positive electrode sheet, the easily decomposable carbonate and the sodium hydroxide are mixed and heated, and after the temperature reaches the melting point of PVDF, the PVDF begins to change from solid to liquid; step B30, as the temperature further increases and reaches the melting point of sodium hydroxide, the sodium hydroxide changes from solid to liquid, and corrodes the surface of the aluminum foil, causing the gap to increase; step B40, and the carbonate enters the gap; step B50, decomposes in a high temperature environment to produce carbon dioxide, further expanding the gap; step B60, as the decomposition reaction proceeds, more and more carbon dioxide is produced, and the gap between the positive electrode material and the aluminum foil becomes larger and larger until they are completely separated.
[0056] In this embodiment, the positive electrode sheet of the waste lithium-ion battery, the easily decomposable carbonate and the sodium hydroxide are mixed and heated. As the temperature rises and reaches the melting point of the binder, the binder in the positive electrode sheet changes from solid to liquid, so that the bonding force becomes weaker, and a micro-crack appears between the aluminum foil of the positive electrode sheet and the positive electrode material; as the temperature further rises and reaches the melting point of the sodium hydroxide, the sodium hydroxide also changes from solid to liquid; at this time, the sodium hydroxide flows into the micro-crack between the aluminum foil and the positive electrode material, and begins to corrode the surface of the aluminum foil in small amounts, so that the gap between the aluminum foil and the positive electrode material is enlarged, and more easily decomposable carbonates enter the gaps, and produce carbon dioxide bubbles through the decomposition of the carbonates, which further increases the gap between the aluminum foil and the positive electrode material, and finally separates the aluminum foil and the positive electrode material to obtain a mixed material; and then the mixed material is screened to obtain separated positive electrode materials, thereby realizing the separation and recovery of the positive electrode materials. Since the heating temperature in the separation process only needs to reach the decomposition temperature of the easily decomposable carbonate, there is no need to gasify the binder, so the separation temperature is greatly reduced, thereby reducing the energy consumption in the separation process; and no waste gas or waste water is generated in the process, which is environmentally friendly and will not affect the chemical properties of the positive electrode material, creating favorable conditions for the subsequent reuse of the positive electrode material.
[0057] In order to enable the details and operations of the above embodiments of the present application to be clearly understood by those skilled in the art, as well as to demonstrate the significant improvement in the performance of the method for separating positive electrode materials from waste lithium-ion batteries in the embodiments of the present application, the above technical scheme is illustrated by means of multiple embodiments below.
[0058] Example 1
[0059] (1) Crushing the lithium nickel cobalt manganese oxide positive electrode sheets of waste lithium-ion batteries into 1-5 mm long strips to obtain original positive electrode sheets;
[0060] (2) placing the positive electrode sheet, sodium hydroxide and zinc carbonate in a nitrogen furnace, mixing them, and heating them to 350°C for 35 min; then maintaining the temperature at 350°C for 30 min to obtain a mixed material, wherein the mass ratio of the positive electrode sheet, sodium hydroxide and zinc carbonate is 1:3:5;
[0061] (3) The mixed material is screened to obtain separated positive electrode materials, wherein the separation rate of the positive electrode material and the aluminum foil is 96.84%.
[0062] The positive electrode material obtained in Example 1 was analyzed for components. The results are as follows: Figure 3 As shown, according to Figure 3 It can be seen from the content that the positive electrode material after separation does not contain aluminum, thus achieving effective separation between the positive electrode material and the aluminum foil.
[0063] Example 2
[0064] (1) crushing the lithium iron phosphate positive electrode sheets of waste lithium-ion batteries into 6-10 mm long strips to obtain original positive electrode sheets;
[0065] (2) placing the positive electrode sheet, sodium hydroxide and magnesium carbonate in a nitrogen furnace, mixing them, and heating them to 450°C for 45 min; then maintaining the temperature at 450°C for 20 min to obtain a mixed material, wherein the mass ratio of the positive electrode sheet, sodium hydroxide and zinc carbonate is 1:1:3;
[0066] (3) The mixed material is screened to obtain separated positive electrode materials, wherein the separation rate of the positive electrode material and the aluminum foil is 98.93%.
[0067] Example 3
[0068] (1) The lithium cobalt oxide positive electrode sheets of the waste lithium-ion batteries are crushed into 2-8 mm long strips to obtain the original positive electrode sheets;
[0069] (2) placing the positive electrode sheet, sodium hydroxide and magnesium carbonate in a nitrogen furnace, mixing them, and heating them to 380°C for 40 min; then maintaining the temperature at 380°C for 10 min to obtain a mixed material, wherein the mass ratio of the positive electrode sheet, sodium hydroxide and zinc carbonate is 1:5:2;
[0070] (3) The mixed material is screened to obtain separated positive electrode materials, wherein the separation rate of the positive electrode material and the aluminum foil is 97.72%.
[0071] Comparative Example 1
[0072] (1) Crushing the lithium nickel cobalt manganese oxide positive electrode sheets of waste lithium-ion batteries into 1-5 mm long strips to obtain original positive electrode sheets;
[0073] (2) placing the positive electrode sheet, sodium hydroxide and zinc carbonate in a nitrogen furnace, mixing them, and heating them to 350°C for 35 min; then maintaining the temperature at 350°C for 30 min to obtain a mixed material, wherein the mass ratio of the positive electrode sheet, sodium hydroxide and zinc carbonate is 1:2:1;
[0074] (3) The mixed material is screened to obtain separated positive electrode materials, wherein the separation rate of the positive electrode material and the aluminum foil is 70.15%.
[0075] Comparative Example 2
[0076] (1) Crushing the lithium nickel cobalt manganese oxide positive electrode sheets of waste lithium-ion batteries into 1-5 mm long strips to obtain original positive electrode sheets;
[0077] (2) placing the positive electrode sheet, sodium hydroxide and zinc carbonate in a nitrogen furnace, mixing them, and heating them to 350°C for 35 min; then maintaining the temperature at 350°C for 30 min to obtain a mixed material, wherein the mass ratio of the positive electrode sheet, sodium hydroxide and zinc carbonate is 1:0.5:5;
[0078] (3) The mixed material is screened to obtain separated positive electrode materials, wherein the separation rate of the positive electrode material and the aluminum foil is 65.36%.
[0079] According to the above-mentioned Examples 1-3 and Comparative Examples 1-2, the method for separating positive electrode materials from waste lithium-ion batteries of the present application can effectively separate the positive electrode materials from the aluminum foil, realize the efficient recycling of the positive electrode sheets, and the recycling process is simple, the process cost is low, and it has good economic benefits.
[0080] The above are only preferred embodiments of the present application, and do not limit the scope of the present application. For those skilled in the art, the present application may have various changes and modifications. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the scope of patent protection of the present application.
Claims
1. A method for separating positive electrode materials from waste lithium-ion batteries, characterized in that: The method comprises the following steps: The positive electrode sheet of the waste lithium-ion battery, the easily decomposable carbonate and sodium hydroxide are mixed and heated to obtain a mixed material, wherein the decomposition temperature of the easily decomposable carbonate is 200-500° C., and the heating temperature is 320-500° C.; The mixed material is screened to obtain separated positive electrode materials.
2. The method for separating positive electrode materials from waste lithium-ion batteries according to claim 1, characterized in that: The easily decomposable carbonate includes at least one of zinc carbonate, magnesium carbonate, copper carbonate and nickel carbonate.
3. The method for separating positive electrode materials from waste lithium-ion batteries according to claim 1, characterized in that: The heating time of the heating is: 20-60 min.
4. The method for separating positive electrode materials from waste lithium-ion batteries according to claim 1, characterized in that: The mass ratio between the positive electrode sheet and the easily decomposable carbonate is 1:(1-5).
5. The method for separating positive electrode materials from waste lithium-ion batteries according to claim 1, characterized in that: The mass ratio between the positive electrode sheet and the sodium hydroxide is 1:(2-10).
6. The method for separating positive electrode materials from waste lithium-ion batteries according to claim 1, characterized in that: The step of mixing and heating the positive electrode sheet of the waste lithium-ion battery, the easily decomposable carbonate and the sodium hydroxide to obtain the mixed material comprises: The positive electrode sheet, the easily decomposable carbonate and the sodium hydroxide are mixed and heated, and then kept warm for 10-30 minutes to obtain the mixed material.
7. The method for separating positive electrode materials from waste lithium-ion batteries according to any one of claims 1 to 6, characterized in that: The positive electrode sheet includes: at least one of a lithium iron phosphate positive electrode sheet, a nickel cobalt manganese positive electrode sheet and a lithium cobalt oxide positive electrode sheet.
8. The method for separating positive electrode materials from waste lithium-ion batteries according to any one of claims 1 to 6, characterized in that: Before the step of mixing and heating the positive electrode sheet of the waste lithium-ion battery, the easily decomposable carbonate and the sodium hydroxide, the method further comprises: Mechanically disassembling the waste lithium-ion battery to obtain an original positive electrode sheet; The original positive electrode sheet is cut into pieces of a preset size to obtain the positive electrode sheet.
